Faktor-faktor yang Mempengaruhi Kompetensi Kerja Karyawan - Aris Wijayanto; Musa Hubeis; M. Joko Affandi; Aji Hermawan (Institut Pertanian Bogor, 2011)
The purpose of this paper is to gain clarity and better understanding on important determinants that contribute to the formulation of employee’s competencies in the workplace. The methodology in this study is using SEM (Structural Equation Model) with two latent variables which are: employee’s soft competency and employee’s hard competency. For each latent variable mentioned, there are several measurable indicators being identified based on theoritical framework and previous studies to be tested. The important findings are: family values, personal’s purpose of life, social environment, accessability for a mentor and formal education, all are important determinants for employee’s soft competency. While training, working experiences, clarity of job description and SMART (Specific, Measurable, Attainable, Relevant and Timebond) objective setting, all are important determinants for employee’s hard competency. From the goodness of fits test to conclude the best recommended model to explain the relationship between main determinants for competencies, main determinants for performance and between competencies and employee’s performance this study succesfully generate a good model which could be useful for both practicioners and researchers on their effort to find ways to further drive employee’s productivity